Oxidative Stress in Preterm Infants: Overview of Current Evidence and Future Prospects - Raffaele Falsaperla; Filadelfo Lombardo; Federica Filosco; Catia Romano; Marco Andrea Nicola Saporito; Federica Puglisi; Ettore Piro; Martino Ruggieri; Piero Pavone (MDPI AG, 2020)
Preterm birth (PTB), defined as parturition prior to 37 weeks of gestation, is the leading cause of morbidity and mortality in the neonatal population. The incidence and severity of complications of prematurity increase with decreasing gestational age and birthweight. The aim of this review study is to select the most current evidence on the role of oxidative stress in the onset of preterm complication prevention strategies and treatment options with pre-clinical and clinical trials. We also provide a literature review of primary and secondary studies on the role of oxidative stress in preterm infants and its eventual treatment in prematurity diseases. We conducted a systematic literature search of the Medline (Pubmed), Scholar, and ClinicalTrials.gov databases, retroactively, over a 7-year period. From an initial 777 articles identified, 25 articles were identified that met the inclusion and exclusion criteria. Of these, there were 11 literature reviews: one prospective cohort study, one experimental study, three case-control studies, three pre-clinical trials, and six clinical trials. Several biomarkers were identified as particularly promising, such as the products of the peroxidation of polyunsaturated fatty acids, those of the oxidation of phenylalanine, and the hydroxyl radicals that can attack the DNA chain. Among the most promising drugs, there are those for the prevention of neurological damage, such as melatonin, retinoid lactoferrin, and vitamin E. The microbiome also has an important role in oxidative stress. In conclusion, the most recent studies show that a strong relationship between oxidative stress and prematurity exists and that, unfortunately, there is still little therapeutic evidence reported in the literature.